Sistem Informasi Perancangan Penyimpanan Berkas pada Kantor Pajak Berbasis Web - Fauziah Fauziah (Yayasan Literasi Sains Indonesia, 2022)
The Tax Service Office (KPP) office which was previously managed by 2 (two) Tax Service Offices (KPP) has become KPP Pratama Jakarta Setiabudi Tiga. PMK Number 55/PMK.01/2007 dated 31 May 2007 concerning Amendments to PMK Number 132/PMK.01/2006. Then in 2015 KPP Pratama Jakarta Setiabudi Tiga was divided into 2 (two) namely KPP Pratama Jakarta Setiabudi Tiga and KPP Pratama Jakarta Setiabudi Empat according to PMK Number 206.2/PMK.01/2014. In storing files at the Tax Office, they still use manuals or keep them in physical form of documents. So there is often loss of documents or it takes a long time in searching for documents so that it interferes with work. Therefore we need an information system system that makes it easier to store and search for these documents. How to make an information system that can speed up employees in searching for the required data. Manual systems that have many weaknesses should be abandoned and switch to a computerized information system. No matter how big the benefits of the development of information technology, to facilitate the development of the system, a web-based system was created.